2019
DOI: 10.1167/iovs.19-27283
|View full text |Cite
|
Sign up to set email alerts
|

Subretinal Drusenoid Deposits in the Elderly in a Population-Based Study (the Montrachet Study)

Abstract: The aim of this study was to investigate the prevalence of subretinal drusenoid deposits (SDD) and to identify associated factors in an elderly population. METHODS. The participants of the population-based Montrachet study underwent an exhaustive ophthalmologic examination, including color fundus photography and macular spectral domain-optical coherence tomography (SD-OCT), coupled with infrared reflectance imaging. The presence of SDD and other age-related macular degeneration lesions, according to the Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…2010; Gabrielle et al. 2019). Imaging studies, applying SD‐OCT and confocal scanning laser ophthalmoscopy, and histological investigations have demonstrated that RPD represent subretinal deposits, which are located internal to the RPE, while conventional drusen are located beneath the RPE (Zweifel et al.…”
Section: Introductionmentioning
confidence: 99%
“…2010; Gabrielle et al. 2019). Imaging studies, applying SD‐OCT and confocal scanning laser ophthalmoscopy, and histological investigations have demonstrated that RPD represent subretinal deposits, which are located internal to the RPE, while conventional drusen are located beneath the RPE (Zweifel et al.…”
Section: Introductionmentioning
confidence: 99%
“…We excluded participants with poor image quality in both eyes and those who suffered from late age-related macular degeneration (AMD). Classification of late AMD was based on both color fundus and OCT images [ 26 ]. From the graphs generated by the software of the modified HRA, we divided the different MP spatial distribution profiles into three groups (ring-like, no ring, and intermediate).…”
Section: Methodsmentioning
confidence: 99%
“…SDDs were graded as present, absent or questionable (those agreed upon as 'questionable' were ultimately graded as absent). A single SDD was deemed sufficient for grading of SDD presence, as per previous studies 32,33 .…”
Section: Classification Of Amdmentioning
confidence: 99%